Persepsi Masyarakat: Politik Kekerabatan pada Pilkada Serentak di Kota Solo - Muhammad Iqbal; Helen Dian Fridayani (Ministry of Home Affairs, 2021)
This paper aims to study the development the dynastypolitics phenomenon in Solo, especially from the public perspectiveafter the 2020 regional head election. Gibran, the son of the Presidentof the Republic of Indonesia ran as a candidate for mayor of Solo.Gibran involvement during the regional head election raised pros andcons in Indonesia. The practice of kinship politics in Indonesia isincreasingly worrying. The reason is that most of the regulations tendto preserve the oligarchy. The flourishing of kinship politics, especiallyin the regions, cannot be separated from the role of political partiesand regulations on regional head election. The study used quantitativeapproach with questionnaires and literature review. The results wereprocessed using SmartPLS 3.0 software with four independentvariable: network strength, position in the party, unequal democracy,and capital. The study showed that only two independent variablesinfluenced the occurrence of kinship politics: network strength andcapital. This led to talks about the community on political issues,President Jokowi, and changed his leadership image, from previouslyseen as a president that does not involve families in political matters.